Las relaciones entre la baja nobleza aragonesa y la casa del rey en el siglo XIV - Mario Lafuente Gómez (Mélanges de la Casa de Velázquez)
This article looks at some of the possibilities offered by the Chancellery and General Treasury series (Archive of the Crown of Aragon) to expand our knowledge of the minor Aragonese nobility in the Late Middle Ages, and more specifically to analyse how the elite of the group fitted into the royal household, between the reigns of Jaime II (1291) and Juan I (1387). For that purpose it offers a detailed description of the records extant in both series then goes on to explore their contents, as an essential step in moving forward some recent lines of research. These include in particular the importance of the military function among the members of the royal family, a portrait of the elite of the Aragonese minor nobility and the economic benefits of their induction into the domus regia.